Pewarnaan Titik Ketakteraturan Lokal Refleksif pada Keluarga Graf Roda - Tommi Sanjaya Putra; Dafik Dafik; Ermita R Albirri (jcgant, 2022)
All graph in this paper is simple and connected graph where V(G) is vertex set and E(G) is edge set. Let function f : V(G){0, 2,..., 2k_v} as vertex labeling and a function f: E(G){1, 2,..., k_e} as edge labeling where k=max{2k_v,k_e} for k_v,k_e are natural number. The weight of vertex u,vV(G) under f is w(u)=f(u)+ Σ_uv E(G) f(uv). In other words, the function f is called local vertex irregular reflexive labeling if every two adjacent vertices has distinct weight and weight of a vertex is defined as the sum of the labels of vertex and the labels of all edges incident this vertex When we assign each vertex of G with a color of the vertex weight w(uv), thus we say the graph G admits a local vertex irregular reflexive coloring. The minimum number of colors produced from local vertex irregular reflexive coloring of graph G is reflexive local irregular chromatic number denoted by χ_lrvs(G). Furthermore, the minimum k required such that χ_lrvs(G)=χ(G) is called a local reflexive vertex color strength, denoted by lrvcs(G). In this paper, we learn about the local vertex irregular reflexive coloring and obtain lrvcs(G) of wheel related graphs.